Smart Waste Management Design for Higher Education: Case Study of Al-Azhar University of Indonesia - Ananta, Aditya; Wirani, Yekti; Sucahyo, Yudho Giri (STMIK Widya Cipta Dharma, 2025)
Al-Azhar University of Indonesia (UAI) has faced significant challenges in waste management. This has caused the UI GreenMetric ranking to be lower. After conducting observations and interviews with the Technical Implementation Unit for Facilities and Infrastructure (SarPras), several major problems found included the absence of waste sorting, excessive waste accumulation, and large waste generation at temporary disposal sites. To improve UAI's ranking in UI Greenmetric and achieve the Sustainable Development Goals target, this study produced a smart waste management system based on the Internet of Things (IoT), Embedded Systems, and Machine Learning (ML). Some of the main components of the design results include a smart bin that uses ultrasonic sensors to reduce accumulation; a web application for monitoring and reward systems; and automatic waste sorting for recycling using Raspberry Pi, infrared sensors, and the ML FOMO (Faster Objects, More Objects) algorithm secured through a CCTV system. In addition, this system is supported by digital education for waste reuse and collection route optimization using ML predictions of the Linear Regression model. With the cooperation of third party sorted waste transportation, this design improves waste management and UAI GreenMetric UI ranking with validation and approval by SarPras and Information Technology Center (PTI).